Analisis Implementasi Project-Based Learning dalam Meningkatkan Keaktifan Siswa Kelas Primary 4 di Kalamullah Al-Qur'an and Multilingual School, Pattani, Thailand - munte, sitinurhaini (Institut Agama Islam Persis Bandung, 2024)
This research aims to increase student learning activity and make the project based learning model a solution to the problem of delivering learning due to language limitations between the two countries. In this research, the type of research used is descriptive research with a quantitative approach. The sample in this research was primary 4th grade students. The results of this research are that the project based learning model gets good results and makes students more active in the learning process. This learning model can facilitate students' understanding without the teacher explaining too much so that PLP activities can run smoothly